1978
DOI: 10.1177/030098587801500508
|View full text |Cite
|
Sign up to set email alerts
|

The Goitrogenic Effect of 4,4'-Oxydianiline in Rats and Mice

Abstract: Abs tract. Fischer 344 rats an d B6C3F t mice were fed diets that conta ined 0.03, 0.06, 0. 1 and 0.2% 4,4'-oxydianiline for 13 week s. The 0. 1 to 0.2% diet caused 40 to 70% mort al ity in female rat s. Altho ug h mice ate abo ut 3.5 time s more ch emi cal tha n rats, no mice died . Alopec ia, dyspn ea a nd cya nosis in rats, an d letha rgy in both species occur red in the 0. 1 to 0.2% gro ups. Goi te r was fou nd in rats tha t d ied as ea rly as the 4th to 5th week of study in th e gro u ps given the 0.06 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…These lesions are consistent with those observed subsequent to chemical or physical thyroidectomy ( 1,3,10,11,15,17,27,29). It has previously been reported that the serum concentrations of T3 and T4 in rats exposed to 12.5 or 50.0 Mg/M3 of 2-MBI were significantly decreased (12).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These lesions are consistent with those observed subsequent to chemical or physical thyroidectomy ( 1,3,10,11,15,17,27,29). It has previously been reported that the serum concentrations of T3 and T4 in rats exposed to 12.5 or 50.0 Mg/M3 of 2-MBI were significantly decreased (12).…”
Section: Discussionsupporting
confidence: 87%
“…Hypertrophic thyrotrophs from the 2-MBI-treated rats closely resembled thyrotrophs from thyroparathyroidectomized rats, as well as those previously described in rats and mice rendered hypothyroid by various means (3,11,15,27). Interestingly, not all hypertrophic thyrotrophs from our study or in previous studies stained immunohistochemically for the 0-chain of TSH.…”
Section: Discussionsupporting
confidence: 82%
“…hormone [1]. Histological examination has revealed hyperplastic and neoplastic changes in the follicular cells with parallel development of pituitary hyperplasia.…”
Section: Toxic Effects and Modes Of Actionmentioning
confidence: 99%
“…In addition, bone marrow hypoplasia and renal microlithiasis developed in the rats; these effects, however, were not dose-dependent. In many of the highest dose group rats the lobular pattern of the liver was accentuated and the pancreas was embedded in clear gelatinous tissue [1,4].…”
Section: Subchronic and Chronic Toxicitymentioning
confidence: 99%